Reframing Pain Management: A Nursing Perspective on Multimodal and Holistic Interventions - Kartika, Imelda Rahmayunia (REAL in Nursing Journal, 2025)
Pain is a multidimensional experience that extends beyond physical discomfort, affecting emotional, psychological, and spiritual domains of human-being health. Nurses are uniquely positioned to play a leading role in multimodal pain management, yet the nursing contribution is often underemphasized in practice and policy. This perspective article synthesizes the evolving understanding of pain management from a nursing perspective and explores the importance of holistic, patient-centered care as nursing interventions. It calls for a shift from biomedical models to integrated approaches, emphasizing non-pharmacologic therapies, cultural competence, and continuous reassessment as vital components of nursing care. Enhancing nursing roles in pain management will improve patient outcomes and address disparities in pain relief.